2005
DOI: 10.1177/107110070502600912
|View full text |Cite
|
Sign up to set email alerts
|

Foot Pressure Measurement Differences Between Boys and Girls With Reference to Hallux Valgus Deformity and Hypermobility

Abstract: The results indicate that there are differences in pressure measurements between boys and girls, but the reasons for these remain unclear. Differences in pressure measurements in the feet of boys and girls may be useful in establishing the cause of foot pathologies for which a prevalence has been shown in boys or girls, such as hallux valgus deformity, which is known to be more frequent in females of all ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
(33 reference statements)
1
22
1
1
Order By: Relevance
“…Interestingly, generating high pressures under the heel was also associated with lower total physical activity and MVPA in boys. An unexpected finding was that girls in the present study generated their highest pressures under the hallux and not the heel (see Figure 2); however, girls have been shown to generate higher pressure under the hallux compared to boys in a previous study [21]. Although high plantar pressures under the hallux were not significantly correlated with physical activity, they had the strongest association with MVPA in girls.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, generating high pressures under the heel was also associated with lower total physical activity and MVPA in boys. An unexpected finding was that girls in the present study generated their highest pressures under the hallux and not the heel (see Figure 2); however, girls have been shown to generate higher pressure under the hallux compared to boys in a previous study [21]. Although high plantar pressures under the hallux were not significantly correlated with physical activity, they had the strongest association with MVPA in girls.…”
Section: Discussioncontrasting
confidence: 52%
“…Independent t-tests were used to determine any differences in the plantar pressure and physical activity variables between boys and girls. In order to establish the strength of the relationships among peak pressure and the physical activity variables, Pearson product moment correlations were calculated for boys and girls separately as foot structure and dynamic pressure patterns have been shown to differ between boys and girls [18][19][20][21]. A relationship was deemed significant at p ≤ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanically, this medial collapse of the midfoot combined with greater force production may result in alteration of functional biomechanics of the metatarsals during the pronation phase of gait, further promoting dissipation of energy at the forefoot. 24 Ferrari and Watkinson 24 found that this was more pronounced in girls than in boys. Medial collapse of the midfoot can alter the biomechanics of the foot during normal gait.…”
Section: Discussionmentioning
confidence: 97%
“…They found that, because of this medial trajectory, the first metatarsal head was loaded more in girls than in boys. 24 Clinically, this may help explain why females are more susceptible than males to hallux valgus disorders. 24 This medial collapse of the midfoot region and resultant pes planus with increased loading at the first metatarsal head also may alter the mechanical advantage of the peroneus longus muscle, leading to decreased eversion and plantar flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation